2017
DOI: 10.1136/bjsports-2016-097283
|View full text |Cite
|
Sign up to set email alerts
|

Injury epidemiology of tennis players at the 2011–2016 Australian Open Grand Slam

Abstract: Investigation of injury at the Australian Open suggests that females are more commonly injured than males. Upper and lower extremity injuries affected females while lower limb injuries were more prominent in males. There was an increasing rate of in-event treatments of upper limb and torso injuries as well as stress fractures during the observation period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 26 publications
(28 reference statements)
6
27
1
2
Order By: Relevance
“…Males had a higher incidence rate for injuries than females during one outdoor tennis season in Denmark (Winge et al, 1989). Recently, an epidemiological study found that female players were more commonly injured than male players (Gescheit et al, 2017).…”
Section: Evidencementioning
confidence: 99%
“…Males had a higher incidence rate for injuries than females during one outdoor tennis season in Denmark (Winge et al, 1989). Recently, an epidemiological study found that female players were more commonly injured than male players (Gescheit et al, 2017).…”
Section: Evidencementioning
confidence: 99%
“…Lógicamente las acciones técnicas y tácticas en pádel (mayor juego en red y búsqueda de golpeos cortados que impidan golpear al contrario en posiciones cómodas) hacen que el tronco sea una región corporal con mayor implicación que en el tenis. En el caso del género femenino, los resultados coinciden con los de otros estudios, siendo las lesiones del miembro superior las más frecuentes, posiblemente debido a diferencias técnicas y tácticas respecto a los hombres 21,22 .…”
Section: Discussionunclassified
“…Por otro lado, los jugadores de menor nivel presentan una peor ejecución técnica en los golpeos 20 , que podría influir también en la aparición de lesiones en este tipo de jugadores. Las lesiones de hombro y codo son las más comunes en deportes donde se realizan golpeos por encima de la cabeza 21 , como es el caso del pádel, y es en los menores niveles de juego donde más golpeos se producen por encima del hombro debido a la utilización del globo como medio defensivo 19 .…”
Section: Discussionunclassified
“…However, given the streams of data now available, it seems timely to revisit whether this recommended choice of exposure remains as pertinent as it once was? Gescheit et al [3] recently highlighted how the choice of exposure can influence study conclusions. For example, when comparing female muscle injury rates using game exposures (strongly correlated to match duration) versus set exposures at the Australian Open between 2011-16, they found 14% variation in the number of reported injuries over time.…”
Section: Discussionmentioning
confidence: 99%
“…We analysed a subset of Gescheit et al [3] Table 1 here *** Match duration was only moderately related to hitting volume (r 2 = 0.37) and match distance (r 2 = 0.30), with only 37% and 30% of the respective variance explained. This questions the use of match duration as the gold standard measure of injury exposure at the professional level.…”
Section: Discussionmentioning
confidence: 99%